A Reminder for a Very Rare Entity: Massive Tongue Swelling after Posterior Fossa Surgery - Hassani, Yassine EL; Narata, Ana Paula; Pereira, Vitor Mendes; Schaller, Carlo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Objective The purpose of this study is to report a case of presumably neurogenic macroglossia that occurred after surgical trapping of a vertebral artery (VA)–posteroinferior cerebellar artery aneurysm, and to analyze its potential pathogenesis.Clinical presentation A 53-year-old woman who suffered from headaches and intermittent loss of consciousness but without evidence of subarachnoid hemorrhage was admitted. Magnetic resonance imaging and angiography showed an irregular aneurysm in the fourth segment of a left dominant VA.Intervention Surgical treatment was indicated after discussion with the neuroradiology team. During surgery, in the prone position the aneurysm ruptured. The patient became hemodynamically instable. On the first postoperative day, macroglossia appeared and remained for 3 weeks until spontaneous regression.Conclusion Macroglossia is a rare complication following neurosurgical procedures with very few cases reported so far. It has been attributed to the sitting position and venous flow congestion. We illustrate a case of macroglossia, which occurred following surgery in the prone position. Its etiology remains speculative, but a neurogenic explanation seems most plausible.
Keywords: macroglossia; posterior fossa surgery; hemodynamic instability